Triple Antibiotic Paste: Boon to Dentistry (Academia Journal of Medicine, 2023)
Microorganisms must be removed from the root canal  (RC) and periapical region for endodontic success. A  sterile state cannot be achieved with only endodontic  instrumentation. Local administration of antibiotics  has been studied in light of the development of non instrumentation endodontic treatment, tissue healing  and lesion sterilization. Triple antibiotic paste (TAP)  with metronidazole, ciprofloxacin, and minocycline  works well for non-vital young permanent teeth and  the RC pathogen. Present review of literature aims to  discuss role of TAP in endodontic treatment.
Keywords: Endodontic treatment; TAP; Antibiotic